Stuktur Internal Organ Reproduksi Tumbuhan Berbiji - Romli Romli; Sani Shofi Mutmainah; Sri Ajeng Mulyani; Vutri Suci Fatimah; Yulia Agustin; Ita Fitriyyah (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Seed plants (Spermatophyta) are a group of plants with a very high level of diversity and are widely distributed throughout the world. This group of plants is known as higher plants or Phanerogamae, namely plants that have seeds and reproduce sexually. Spermatophyta can be divided into two main groups, namely Gymnospermae or plants that have characteristics of open seeds and Angiospermae or plants that have characteristics of closed seeds. Research on the structure of internal reproductive organs of seed plants was carried out at the Instructional Laboratory 1 on Campus I UIN SGD Bandung, Cipadung Village, Cibiru District, Bandung City, West Java Province. Qualitative methods were used in this study by conducting direct observations on the objects being observed. This study aims to see and observe how the reproductive structure is in seed plants. Based on data from observations made on paper flowers (Bougainvillea), the flower has no petals, 3 crowns attached to 27 stamens, and 4 pistils with the flower formula K0 [C3 A27] G4. Meanwhile, in the study of lilies (Crinum jagus) have 5 petals, 6 crowns attached to 6 stamens, and 1 pistil with a flower formula of K5 [C6 A6 ] G1.